(untitled) (The Journal of Medicine, Humanity and Media, 2025)
On 6 July 2025, Panel 1—“Adoption, Processing, and Persuasion Mechanisms of Health Information in Digital Media”—took place during the 8th “Medicine, Humanity and Media” Health Communication International Conference at Peking University. Six early‑career scholars—Yinglin Wang (City University of Hong Kong), Haoning Xue (University of Utah), Fen Zhou and Xincheng Huang (South China University of Technology), Yanpei Chen (University of Texas at Austin), and Haoyu Wang (Renmin University of China)—shared new empirical work on digital health communication. Drawing on a survey of Chinese young adults, Y. Wang found that adoption of parental online health advice depends more on relational closeness than on perceived credibility. Using eye‑tracking with 1,467 U.S. participants, Xue observed an inverted‑U effect in which moderate message‑sensation value in short videos maximized attention, cognitive engagement, and risk perception. Through a 2 × 2 factorial experiment, Zhou showed that inoculation messages reduce worries about vaccine side‑effects and PET‑CT radiation and, via attitude change, increase behavioural intent. Huang demonstrated that internally activated moral licensing has a greater impact on responsible‑drinking intentions than external gain–loss framing. From 27 qualitative interviews, Chen revealed how patriarchal ideologies across family, institutional, and online arenas silence women in gynaecological health, producing informational and care disparities. Finally, H. Wang used latent‑profile analysis to identify adaptive, anxious, and dysregulated cyberchondria subtypes; rural residence and low income predicted membership in the dysregulated group, marked by a maladaptive search–anxiety cycle driven by brooding and avoidance.